Feasibility of Chrysanthemum Farming in Tomohon City - Christy Adeleine Lagana; Dwidjono Hadi Darwanto; Masyhuri Masyhuri (Agro Ekonomi, 2018)
This research entitled “Feasibility of Chrysanthemum Farming in Tomohon City”. Chrysanthemum is one of floriculture commodities that people are interested and popular due to its many species and its beautiful shape and colour. Tomohon is a town in North Sulawesi Province that having potential to develop cut flower chrysanthemum. This research was intended to identify cost and income of chrysanthemum farming in Tomohon and its farming feasibility. Cost and income approach was used to identify costs and income of chrysanthemum farming in Tomohon, while feasibility of chrysanthemum farming was analyzed using R/C ratio, π/C ratio and break even point analysis. Sample was taken using simple random sampling in 4 Villages on North Tomohon Sub-district that is centre of chrysanthemum farming in Tomohon. Results of the research indicated that cost for the chrysanthemum farming is Rp 128,330,475.42 per farming per year, while its income reaches Rp 169,750,054.50 per farming per year. Result of feasibility study indicated that chrysanthemum farming in Tomohon has R/C ratio of 2.63 (R/C >1), p/C ratio of 113.58% (p/C>9%), and feasible BEP, where BEP of revenue of Rp 27,472,521.11 (farming  revenue Rp 274,086,000 per year), BEP of production of 9,156 stems (production 91,362 stems per year) and BEP of price of Rp 1,142.01 per stem (price Rp 3,000 per stem). Therefore, chrysanthemum farming in Tomohon is profitable and feasibly to develop.